SĂPTĂMÂNA CREATIVITĂȚII ȘI INOVAȚIEI 2016: AUTOEVALUARE ȘI EVALUARE CU COMENTARII - KULIKOVSKI, Lidia (BIBLIOPOLIS, 2020)
The Muncipal Library joined the global movement for creativity and innovation Creativity and Innovation World Week, held every year between April 15 to 21. The second edition Hasdeu Creativity and innovation week’s was attended by 20 branches and three departments. The purpose of Creativity and Innovation Week, edition 2016, was to mobilize, to encourage librarians to work for one week, otherwise, to transform our library into a creative environment, involving users in innovation activities. The article highlights, commenting, concluding the results of self-assessment performed by СIW participants themselves. The results are revealing: the Creativity and Innovation Week 2016 proved a good strategy to motivate the librarians to reveal the skills, talents, distinct feelings that they have not even suspected. CIW has provided the freedom to experience new things and ideas and to evaluate oneself, it was a school of creativity and innovation. During the week the professional librarians understood that education is the key to future innovation.